Pyrolysis production of fruit peel biochar for potential use in treatment of palm oil mill effluent - Lam, Su Shiung; Cheng, C. K.; Liew, Rock Keey; Nazaitulshila, Rasit; Ooi, Chee Kuan; Ma, Nyuk Ling; Ng, Jo Han; Lam, Wei Haur; Chong, Cheng Tung; Chase, Howard A. (Academic Press, 2018)
Fruit peel, an abundant waste, represents a potential bio-resource to be converted into useful materialsinstead of being dumped in landﬁll sites. Palm oil mill efﬂuent (POME) is a harmful waste that shouldalso be treated before it ca n safely be released to the environment. In this study, pyrolysis of banana andorange peels was performed under different temperatures to produce biochar that was then examined asadsorbent in POME treatment. The pyrolysis generated 30.7e47.7 wt% yield of a dark biochar over atemperature ranging between 400 and 500C. The biochar contained no sulphur and possessed a hardtexture, low volatile content (34 wt%), and high amounts of ﬁxed carbon (72 wt%), showing durabilityin terms of high resistance to chemical reactions such as oxidation. The biochar showed a surface area of105 m2/g and a porous structure containing mesopores, indicating its potential to provide manyadsorption sites for use as an adsorbent. The use of the biochar as adsorbent to treat the POME showed aremoval efﬁciency of up to 57% in reducing the concentration of biochemical oxygen demand (BOD),chemical oxygen demand COD, total suspended solid (TSS) and oil and grease (O&G) of POME to anacceptable level below the discharge standard. Our results indicate that pyrolysis shows promise as atechnique to transform banana and orange peel into value-added biochar for use as adsorbent to treatPOME. The recovery of biochar from fruit waste also shows advantage over traditional landﬁll approachesin disposing this waste.